A Review of the Design and Implementation of a Hybrid Cardiac Rehabilitation Program: AN EXPANDING OPPORTUNITY FOR OPTIMIZING CARDIOVASCULAR CARE. Issue 1 (January 2022) - Keteyian, Steven J.; Ades, Philip A.; Beatty, Alexis L.; Gavic-Ott, Anne; Hines, Stephen; Lui, Karen; Schopfer, David W.; Thomas, Randal J.; Sperling, Laurence S.
Abstract : Purpose: This review describes the considerations for the design and implementation of a hybrid cardiac rehabilitation (HYCR) program, a patient-individualized combination of facility-based cardiac rehabilitation (FBCR) with virtual cardiac rehabilitation (CR) and/or remote CR. Review Methods: To help meet the goal of the Millions Hearts Initiative to increase CR participation to 70% by 2022, a targeted review of the literature was conducted to identify studies pertinent to the practical design and implementation of an HYCR program. Areas focused upon included the current use of HYCR, exercise programming considerations (eligibility and safety, exercise prescription, and patient monitoring), program assessments and outcomes, patient education, step-by-step instructions for billing and insurance reimbursement, patient and provider engagement strategies, and special considerations. Summary: A FBCR is the first choice for patient participation in CR, as it is supported by an extensive evidence base demonstrating effectiveness in decreasing cardiac and overall mortality, as well as improving functional capacity and quality of life. However, to attain the CR participation rate goal of 70% set by the Million Hearts Initiative, CR programming will need to be expanded beyond the confines of FBCR. In particular, HYCR programs will be necessary to supplement FBCR and will be particularly useful for the many patients with geographic or work-related barriers to participation in an FBCR program. Research is ongoing and needed to develop optimal programming for HYCR. Abstract : This was a targeted review of studies pertinent to the practical design and implementation of a hybrid cardiac rehabilitation program. Areas focused upon included exercise programming (eligibility and safety, exercise prescription, and patient monitoring), program assessments and outcomes, patient education, billing and insurance reimbursement, and patient and provider engagement strategies.